ANALISIS PENGARUH PEMAHAMAN AKUNTANSI DAN KEAKTIFAN MAHASISWA TERHADAP PENYUSUNAN LAPORAN KEUANGAN SESUAI SAK KASUS PADA MAHASISWA JURUSAN AKUNTANSI STIE PANCASETIA - Imawati Yousida (Jurnal Ilmiah Ekonomi Bisnis, 2020)
This research aims to analyze influence understanding of accounting and student activeness towards the preparation of financial statement in accordance with The Financial Accounting Standards: case study in accounting department students STIE Pancasetia.The research method used quantitative with analytical techniques used are multiple linear regression.The population and sample used were fifty-seven seventh of students majoring in accounting.The results shows understanding of accounting and student activity simultaneously and partially have a significant effect on the preparation of financial statements in accordance with The Financial accounting standards.While the dominant variable influences the understanding of accounting.Understanding of accounting as the basic of basic accounting knowledge in the process of preparing financial reporting.So the advice given to the object of the research is expected to develop the level of understanding of students by developing learning that is more varied and consistent, especially in accounting practices, the completion of case studies related to the preparation of financial reports in accordance with financial accounting standards and for students to be able to increase their activity in the learning process such as actively asking questions, issuing opinions and sharing experiences related to accounting. As well as independent practice and critical thinking towards accounting developments in the future.Keyword : Understanding of Accounting, Student Activity, Preparation of Financial Statements in Accordance, Financial Accounting Standards.